2008
DOI: 10.1097/aog.0b013e31817615a0
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical Foley Catheter With and Without Oxytocin for Cervical Ripening

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As concomitant administration of prostaglandin and oxytocin is strictly forbidden to prevent the risk of tachysystolia or uterine hyperstimulation [ 21 ], oxytocin may be administrated earlier when used in combination with mechanical devices, positively impacting the period of time before birth. Finally, the combination of catheter plus oxytocin has not been shown to impact rates of caesarean section, postpartum hemorrhage, or neonatal complications [ 19 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As concomitant administration of prostaglandin and oxytocin is strictly forbidden to prevent the risk of tachysystolia or uterine hyperstimulation [ 21 ], oxytocin may be administrated earlier when used in combination with mechanical devices, positively impacting the period of time before birth. Finally, the combination of catheter plus oxytocin has not been shown to impact rates of caesarean section, postpartum hemorrhage, or neonatal complications [ 19 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a trial comparing the Foley catheter with or without oxytocin used a low-dose oxytocin regimen for induction and augmentation that was specific to that institution. 81 This trial found that the addition of oxytocin to the Foley catheter did not shorten the time to delivery. However, subsequent studies that used a higher dose of oxytocin per institutional protocol reported a shorter time to delivery with the combination method.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 93%
“…Of the 103 trials identified, just 63 were RCTs. 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 The majority of RCTs were single-center trials conducted in academic hospitals, which can limit the generalizability of the results to other community-based populations. Among the 12 multicenter trials, the number of centers ranged from 2 to 49 and tended to include both university-affiliated and community hospitals.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
See 2 more Smart Citations